Speed and agility predictors among adolescent male football players - França, Cíntia (2022)
This study aimed to examine the associations between lower-body explosive strength (squat jump—SJ, and countermovement jump—CMJ), speed (10- and 35-m linear sprints), and agility (t-test) capacities, after controlling for crucial predictors such as chronological age (CA) and body composition. The sample was composed of 164 adolescent male football players from under 19, under 17, and under 15 age groups. Body fat percentage (BF%) was significantly and positively related to body mass, speed, and agility. In contrast, BF% was a significant negative predictor of lower-body explosive strength. Sprint and t-test times were significantly and negatively correlated with lower-body explosive strength. After controlling for CA and body composition, SJ was the most significant predictor, accounting for 36 to 37% of the variance observed in the 35 m linear sprint and the t-test performance. Our main results suggest that lower-body explosive strength, particularly in the SJ, is a significant predictor of male adolescent male football players’ speed and agility capacities. Conversely, detrimental relationships between BF% and these outcomes were observed. Sports agents should consider lower-body explosive strength development as part of the youth football training process, particularly to improve maximal sprint and change of direction times, which are crucial to game performance.